2019
DOI: 10.1109/access.2019.2947067
|View full text |Cite
|
Sign up to set email alerts
|

Toward Edge-Assisted Video Content Intelligent Caching With Long Short-Term Memory Learning

Abstract: Nowadays video content has contributed to the majority of Internet traffic, which brings great challenge to the network infrastructure. Fortunately, the emergence of edge computing has provided a promising way to reduce the video load on the network by caching contents closer to users.But caching replacement algorithm is essential for the cache efficiency considering the limited cache space under existing edge-assisted network architecture. To investigate the challenges and opportunities inside, we first measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Videos combine images, sounds and words that can be presented in different ways and at different lengths to facilitate learning [32]. Many studies in recent years have shown the benefits of using video in the classroom [33,34], as the multimedia factor turns any new element in the learning process into long-term memory learning [35].…”
Section: Introductionmentioning
confidence: 99%
“…Videos combine images, sounds and words that can be presented in different ways and at different lengths to facilitate learning [32]. Many studies in recent years have shown the benefits of using video in the classroom [33,34], as the multimedia factor turns any new element in the learning process into long-term memory learning [35].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [59] considered the video propagation as well as popularity evolution patterns and developed an integration of ARIMA, multiple linear regression (MLR), and k-nearest neighbor regression (kNN) to predict the social patterns to improve caching performance. Zhang et al [60] proposed an intelligent edge-assisted caching framework LSTM-C based on LSTM to better learn to content popularity patterns both at long and short time scale. Zhu et al [61] proposed to leverage DRL to automatically learn an end-to-end caching policy, where the user requests, network constraints, and external information are all embedded in the learning environment.…”
Section: ) Cachingmentioning
confidence: 99%
“…Zhou et al ( 2019 ) presented a system that predicts sunlight and estimates the electricity produced by solar power systems through LSTM, which becomes the basis of solar power equipment management. Finally, Zhang et al ( 2019 ) utilized LSTM in edge computing; when video files are too large, an LSTM technique helps predict the buffer memory for each edge computing, node. Guardo et al ( 2018 ) mainly used Fog Computing to reduce the workload of centralized servers.…”
Section: Related Workmentioning
confidence: 99%